PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KARYAWAN SERTA IMPLIKASINYA TERHADAP KINERJA - Stevianus X Mentang (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
The purpose of this study was to determine the direct effect of reward on motivation. Reward for performance. Punishment on motivation. Punishment on performance. Motivation for performance. And to know the indirect effect of reward on performance through motivation. Punishment on performance by means of motivation. This research uses quantitative methods with associative analysis. Population of 58 people. Sampling using saturated sampling method. The data obtained were obtained through a questionnaire with a Likert scale. Research data processing using analysis of Structural Equation Modeling (SEM) with SmartPLS 3.0. The data analysis technique used two approaches, namely testing the Outer Model measurement model and the second testing the Inner Model structural model. The results showed that 1) Reward has a significant and positive effect on motivation. 2) Rewards have a significant and positive effect on performance. 3) Punishment has a positive and significant effect on motivation. 4) Punishment has a negative and insignificant effect on performance. 5) Motivation has a positive and significant effect on performance 6) Motivation mediates part of the effect of reward on performance 7) Motivation mediates the effect of punishment on performance.